Studies in Fat Grafting. Issue 4 (April 2015) - Garza, Rebecca M.; Rennert, Robert C.; Paik, Kevin J.; Atashroo, David; Chung, Michael T.; Duscher, Dominik; Januszyk, Michael; Gurtner, Geoffrey C.; Longaker, Michael T.; Wan, Derrick C.
<x xml:space="preserve">Abstract</x> Background: Fat graft volume retention remains highly unpredictable, but addition of adipose-derived stromal cells to fat grafts has been shown to improve retention. The present study aimed to investigate the mechanisms involved in adipose-derived stromal cell enhancement of fat grafting. Methods: Adipose-derived stromal cells isolated from human lipoaspirate were labeled with green fluorescent protein and luciferase. Fat grafts enhanced with adipose-derived stromal cells were injected into the scalp and bioluminescent imaging was performed to follow retention of adipose-derived stromal cells within the fat graft. Fat grafts were also explanted at days 1, 5, and 10 after grafting for adipose-derived stromal cell extraction and single-cell gene analysis. Finally, CD31 immunohistochemical staining was performed on fat grafts enriched with adipose-derived stromal cells. Results: Bioluminescent imaging demonstrated significant reduction in luciferase-positive adipose-derived stromal cells within fat grafts at 5 days after grafting. A similar reduction in viable green fluorescent protein–positive adipose-derived stromal cells retrieved from explanted grafts was also noted. Single-cell analysis revealed expression of multiple genes/markers related to cell survival and angiogenesis, including BMPR2, CD90, CD105, FGF2, CD248, TGFß1, and VEGFA. Genes involved in adipogenesis were not expressed by adipose-derived stromal cells. Finally, CD31 staining revealed significantly higher vascular density in fat grafts explanted at day 10 after grafting. Conclusions: Although adipose-derived stromal cell survival in the hypoxic graft environment decreases significantly over time, these cells provide multiple angiogenic growth factors. Therefore, improved fat graft volume retention with adipose-derived stromal cell enrichment may be attributable to improved graft vascularization.